Theoretical foundation of the management of the quality in professional training of future Informational Technology teachers - Kravchenya, A. (Problems of Engineer-Pedagogical Education, 2018)
The author’s model of the management system of the quality in professional training of future Informational Technology teachers is offered in the article. Based on the analysis of scientific methodical and management scientific researches of native scientists and the surveyed respondents, the criteria of the management of the quality in professional training of future Informational Technology teachers are determined as the following motivational value, cognitiveprofessional, organizational-managerial. The indicators are described and the levels are offered (reproductive, constructive and creative). It is proved that to improve the effectiveness of the management of the quality in professional training of future Informational Technology teachers the model of the management system of the quality in their professional training should be developed and consist of five interrelated components: professional substantial, managerial, organizational, technological, diagnostic, regulative (on request). The connecting-link for all the system components is the organizational and pedagogical conditions of the management of the quality in professional training of future Informational Technology teachers.